Transformational Leadership, Affective Trust, Intrinsic Motivation, and creativity: An analysis of Vietnam’s Self-Financed Public Universities - Huynh Thi Thu , Suong; Ho Xuan , Tien (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The purpose of the study is to explore the relationship between the factors Transformational leadership, Affective trust, Intrinsic motivation, and Creativity. Conducting this research at self-finance public universities in Vietnam by combining the qualitative and quantitative methods. Data were collected via questionnaire reference. Research results show that Transformational leadership and Affective trust have positive relationships with Intrinsic motivation and Creativity, Transformational leadership has a positive relationship with Affective trust, Intrinsic motivation has a positive relationship with Creativity, Intrinsic motivation is the mediating variable affecting the impact of Transformational leadership and Affective trust on Creativity, Affective trust is the mediating variable influence on the effect of Transformational leadership on Creativity. As a result, early relief helps important leaders into the role of the prefix of Transformational leadership as the origin to Affective trust, Intrinsic motivation, Creativity to enhance creativity thereby improving the quality of higher education. Research results are expected to fill an important gap on the theory of human capital in Vietnamese self-finance public higher education.
Keywords: Transformational leadership; Affective trust; Intrinsic motivation; Creativity; Self-finance public universities